Determination of Water Quality Index and Suitability of Shatt Al Arab River and Treated Water for Some Water Treated Plants in Basrah - Al-Badran, Fatima A. A. (Basrah Journal for Engineering Sciences, 2013)
Shatt Al-Arab River is the main water source for all water treatment plants in Basrah governorate. In order to assess its suitability as a source for domestic water supply and the performance of some of main water treatment plants, water quality index (WQI) is obtained for both raw and treated water for 10 water treatment plants. Physic-chemical parameters were monitored for the calculation of WQI for Winter, Spring, Summer, and Autumn seasons from March- 2011 to March- 2012.The parameter which were taken into account for the present work are pH, turbidity, electric conductivity, total alkalinity, total hardness, Ca, Mg, Cl, SO4, TDS, Na, and K. The results indicate that Shatt Al Arab is very poor for domestic, industrial, and irrigation purposes during Winter, Spring, Summer, and Autumn seasons, while seven of ten of consider of water treatment plants produce water of poor quality.